2017
DOI: 10.1523/jneurosci.0943-17.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Conditional Deletion ofRic-8bin Olfactory Sensory Neurons Leads to Olfactory Impairment

Abstract: The olfactory system can discriminate a vast number of odorants. This ability derives from the existence of a large family of odorant receptors expressed in the cilia of the olfactory sensory neurons. Odorant receptors signal through the olfactory-specific G-protein subunit, Gαolf. Ric-8b, a guanine nucleotide exchange factor, interacts with Gαolf and can amplify odorant receptor signal transduction To explore the function of Ric-8b, we generated a tissue specific knock-out mouse by crossing OMP-Cre transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Consistent with the role of a GEF, Ric-8B is able to amplify odorant receptor signaling or dopamine receptor signaling through Gαolf in cultured cells [2,[7][8][9]. Also, a series of studies indicate that Ric-8B regulates Gα protein abundance in the cells, and suggest that Ric-8B may serve as a chaperone that promotes Gα protein stability and the formation of functional G protein complexes [7,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 69%
“…Consistent with the role of a GEF, Ric-8B is able to amplify odorant receptor signaling or dopamine receptor signaling through Gαolf in cultured cells [2,[7][8][9]. Also, a series of studies indicate that Ric-8B regulates Gα protein abundance in the cells, and suggest that Ric-8B may serve as a chaperone that promotes Gα protein stability and the formation of functional G protein complexes [7,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 69%
“…Gγ13 is a G protein γ subunit that was first isolated from murine taste bud cells 11 . It has been found in the OSNs in the MOE, interacting with Gαolf, Gβ1 to form the heterotrimeric G protein Gαolf/β1/γ13 and transduce olfactory signals 7 , 12 , 15 , 16 . In this study, we investigated its expression pattern over developmental stages and found that both Gγ13 and Gαolf are expressed in the MOE as early as E5, indicating that the olfactory sensation may function in early embryonic stages (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the role of a GEF, Ric-8B is able to amplify odorant receptor signaling or dopamine receptor signaling through Gαolf in cultured cells [2,79]. Also, a series of studies indicate that Ric-8B regulates Gα protein abundance in the cells, and suggest that Ric-8B may serve as a chaperone that promotes Gα protein stability and the formation of functional G protein complexes [7,8,1013].…”
Section: Introductionmentioning
confidence: 87%